Opportunities and Challenges of Engineering Technology Education for Developing Countries - Badhrulhisham, Abdul Aziz (2015)
At the end of presentation, participants will be able to: understand the Engineering Technology Education issues in Malaysia, value the benefits of Engineering Technology to the country, appreciate initiatives in Engineering Technology, experience the challenges faced during the whole process, visualize the Future Direction.